EVALUATION OF THE ANXIETY OF NURSING STUDENTS AT A FOUNDATION UNIVERSITY IN TURKEY - COŞKUN, Adnan Batuhan; ELMAOĞLU, Erhan (Göbeklitepe Medical Science Journal, 2021)
Aim: This study was conducted to evaluate the occupational anxiety of students studying in the classes of the nursing department. Method: In the present study, a survey method was used, and the study was designed in a descriptive and cross-sectional model. The population of the study consists of students studying in the 1st and 4th-grades of a foundation university’s nursing department in the 2019-2020 academic year. In consequence of stratified and cluster sampling, 153 students were included in the sample, and the data of 125 students who agreed to participate in the study were evaluated. Study data “Socio-demographic questionnaire” and “State-Trait Anxiety Inventory” were designed as web-based, and transferred to the sample group via the social media they prefer. Results: According to the data obtained, 38.7% of 1st-grade students and 57.1% of 4th-grade students think that the respect and perception of the society for the profession are media, and 51.6% of 1st-grade students and 54% of 4th-grade students like their profession. The students mostly stated that they were anxious, and 1st-grade students stated that they were most anxious due to violence and difficulties of the profession, and senior students mostly stated that they were anxious about the difficulties of the profession and the possibility of not being appointed. When the State-Trait Anxiety Scale scores are examined, the anxiety of the 1st-grade students was higher than the 4th-grade students, and a significant difference was determined. Conclusion: The occupational anxiety of the students of the nursing department is at a high level, and the occupational anxiety of the students who have just started vocational education is higher than the seniors. Educators should be aware of the occupational anxiety of students and the level of anxiety according to the class, and nursing education programs and the teaching-learning process should be arranged in a way to help reduce professional anxiety.